2022
DOI: 10.3390/su142013568
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Prediction of Urban Online Car-Hailing Travel Demand Based on Transformer Network

Abstract: Online car-hailing has brought convenience to daily travel, whose accurate prediction benefits drivers and helps managers to grasp the characteristics of urban travel, so as to facilitate decisions. Spatiotemporal prediction in the transportation field has usually been based on a recurrent neural network (RNN), which has problems such as lengthy computation and backpropagation. This paper describes a model based on a Transformer, which has shown success in computer vision. The study area is divided into grids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Bi et al [33] successfully identified job-housing sites using online car-hailing data. Notably, machine learning (especially deep learning) methods were also introduced into the study of online car-hailing data, to predict variations in patterns [34], changes in the supply and demand [35], and so on.…”
Section: Studies Based On Online Car-hailing Datamentioning
confidence: 99%
“…Bi et al [33] successfully identified job-housing sites using online car-hailing data. Notably, machine learning (especially deep learning) methods were also introduced into the study of online car-hailing data, to predict variations in patterns [34], changes in the supply and demand [35], and so on.…”
Section: Studies Based On Online Car-hailing Datamentioning
confidence: 99%
“…In order to predict the travel demand of online car-hailing more accurately, Bi et al (2022) proposed a new spatio-temporal prediction method model based on Transformer architecture. Compared with the three most commonly used models, the results show that the model has the best prediction accuracy and prediction accuracy training speed [ 14 ]. With the rapid development of online big data technology and the rise of non-parametric regression models in the field of forecasting, forecasting methods represented by the K-nearest neighbor method have started to be introduced into the field of transportation.…”
Section: Introductionmentioning
confidence: 99%